Chronic Inflammation Disrupts Circadian Rhythms in Splenic CD4+ and CD8+ T Cells in Mice - Misa Hirose; Alexei Leliavski; Leonardo Vinícius Monteiro de Assis; Olga Matveeva; Ludmila Skrum; Werner Solbach; Henrik Oster; Isabel Heyde (Cells, 2024)
Internal circadian clocks coordinate 24 h rhythms in behavior and physiology. Many immune functions show daily oscillations, and cellular circadian clocks can impact immune functions and disease outcome. Inflammation may disrupt circadian clocks in peripheral tissues and innate immune cells. However, it remains elusive if chronic inflammation impacts adaptive immune cell clock, e.g., in CD4+ and CD8+ T lymphocytes. We studied this in the experimental autoimmune encephalomyelitis (EAE), a mouse model for multiple sclerosis, as an established experimental paradigm for chronic inflammation. We analyzed splenic T cell circadian clock and immune gene expression rhythms in mice with late-stage EAE, CFA/PTx-treated, and untreated mice. In both treatment groups, clock gene expression rhythms were altered with differential effects for baseline expression and peak phase compared with control mice. Most immune cell marker genes tested in this study did not show circadian oscillations in either of the three groups, but time-of-day- independent alterations were observed in EAE and CFA/PTx compared to control mice. Notably, T cell effects were likely independent of central clock function as circadian behavioral rhythms in EAE mice remained intact. Together, chronic inflammation induced by CFA/PTx treatment and EAE immunization has lasting effects on circadian rhythms in peripheral immune cells.